Computer English Speech Independent Evaluation System of the Fusion Discrimination Training Algorithm - Jin, Yu Ping (International Journal of Emerging Technologies in Learning (iJET), 2018)
This paper proposes a discriminative training algorithm for autonomous speech evaluation of computer English. Firstly, the mathematical expression of discriminative training algorithm is defined, and the conditions of using the algorithm are deduced. To facilitate the discriminant training algorithm calculation, through the parameter usage and frequency to calculate the algorithm, thus simplifying the discriminative training algorithm for English speech evaluation method. Experimental results show that the proposed discriminative training algorithm is correct for computer English speech independent evaluation.